Leisure activities for the development of creative intelligence in mathematical problem solving - Angelica Mercedes Tumbaco Castro; Galo Ernesto Cabanilla Guerra; Christian Antonio Pavon Brito; Tannia Acosta (OmniaScience, 2018)
The present work studies the influence of leisure activities on the creative intelligence of the students. An experimental pre- and post-test design was carried out with individuals selected in a sampling process. The design identifies the ease of students to place themselves in possible contexts and solve them mathematically through Polya's phases. Two target groups were then located, one of which was applied the independent variable. The results were verified using the variable contrast statistical method, which concluded that leisure activities affect creative intelligence in positive terms, since the experimental group of post-test presented greater success in the entelechy of possible scenarios, facilitating the solving of mathematical problems related to different topics.